Impact of heat stress, molecular responses, and breeding strategies for heat tolerance in cotton (Gossypium hirsutum L.) (Zoo Botanica, 2025)
Cotton is a vital cash crop in many countries due to its multipurpose usage and value addition to Gross Domestic Production (GDP), but due to climate change, it is extremely vulnerable to biotic and abiotic stresses. Among abiotic stresses, heat stress (HS) has emerged as a critical environmental constraint affecting cotton productivity and fiber quality, particularly under the escalating influence of global climate change. HS affects the cotton plant at morphological, physiological and molecular levels such as activation of various microRNAs (miRNAs), reactive oxygen species (ROS), signaling pathways including calcium, kinases, carbohydrates, gene expression regulation, epigenetic regulation, and plant hormones that help mitigate cellular damage. The purpose of this manuscript is to study the impacts of HS at critical stages of plant growth by thorough understanding of underlying mechanisms and regulatory pathways and explore the genetic underpinnings of cotton to aid breeders in employing various strategies such as conventional breeding, molecular and transgenic approaches to enhance thermal resilience. A deeper understanding of these adaptive responses is essential for sustaining cotton production in increasingly warmer climates.
Keywords: Cotton; high temperature; impact; mechanisms; strategies